Influence of Halal Labeling, Religiosity, Taste, and Price Against the Purchase Decision of Korean Instant Noodle Products in Islamic Business Perspective (Study on Muslim Community in Bandar Lampung) - Salsa Azzahra Rusmiyati; Fatih Fuadi; Mia Selvina (Universitas KH. Abdul Chalim Mojokerto, 2025)
The popularity of Korean instant noodles among Indonesian muslims is increasing, but this raises concerns regarding the halal status of these imported products. Some products do not yet have official halal labels from Indonesian institutions, raising doubts and influencing consumer behavior. This study aims to analyze the influence of halal labeling, religiosity, taste, and price on purchasing decisions for Korean instant noodles from an Islamic business perspective. The halal label is understood as a guarantee of product compliance with sharia, religiosity reflects an individual’s obedience in choosing halal products, taste is related to taste preferences, and price reflects consumers’ purchasing power and perceived value. The study used a quantitative approach with data collection techniques through an online questionnaire to 100 muslim respondents in Bandar Lampung, using a purposive sampling technique with the criterion of having purchased Korean instant noodle products. The sample calculation used the Slovin formula with a 0.1 error rate. Data were analyzed using SmartPLS 4. The results show that the halal label, religiosity, taste, and price have a positive and significant effect on purchasing decisions. These findings contribute to business actors in designing marketing strategies that are in accordance with Islamic business principles and the characteristics of muslim consumers.